The Uses of the Past: Political Culture in Early Modern Russia and the Problems of the Present - Martin, Russell E. (The sixteenth century journal, 2019)
The author discusses the various approaches to the study of early modern Russia. He mentions how historical scholarship relates to contemporary politics, the work on Russian kinship by Stepan Borisovich Veselovskii and its role in political culture, and the question of autocracy and its subsequent authoritarian governments.